Educational strategies for the development of psychomotor skills in early childhood students: A systematic review - González Granda, Lorena Marielisa; Lozada Meza , Mariela Libelly; Leon Medrano , Denisse Ivonne; Coto Cazorla , Yessenia Maria (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to analyze educational strategies for the development of psychomotor skills in early childhood students through a systematic review. A qualitative approach was adopted, using recognized academic databases such as Scopus, Redalyc, Scielo, and ProQuest. The search equations employed included combinations of key terms using Boolean operators like "AND" and "OR." The most relevant findings of the review highlight that educational strategies focused on physical activity and psychomotor skills are fundamental for the holistic development of children, as they not only promote motor development but also have a significant impact on cognitive, emotional, and social skills. Personalizing physical activity programs, adapting them to the specific characteristics of each school environment and the individual needs of children, is identified as a key factor for maximizing their effectiveness. Moreover, the importance of early intervention and careful planning of activities is emphasized, where physical, emotional, and cognitive aspects must be integrated simultaneously, creating a holistic learning environment. The integration of physical activities that promote both gross and fine motor skills enables children not only to improve their motor abilities but also to strengthen essential cognitive skills such as memory, attention, and problem-solving.